MULTIBAND SLOTTED APERTURE ANTENNA WITH DEFECTED GROUND STRUCTURE FOR C AND X-BAND COMMUNICATION APPLICATIONS - Bhavani, K V L; Khan, Habibulla; Madhav, B T P (Journal of Theoretical and Applied Information Technology, 2015)
A series of simulations and investigations of slotted microstrip patch antennas with defected ground structure are presented in this article. The analysis includes the effects of varying the dimensions of the feed line, patch and the ground plane. All the investigated antennas are showing good bandwidth enhancement with microstrip feeding method. In this study, different shapes of slots, in U-shape and L-shape are taken in to the account. Among all the examined antennas, proposed slot microstrip patch antenna of dimensions 15X20X1.6 mm with additional slot apertures of U and L combination is providing excellent radiation characteristics at lower frequency band of communication systems.